Emotional production of common sense. Advertising with an aesthetic matrix (Itinera, 2022)
Aesthetics and Economics, both immanent sciences producing sense, conciliate (find an agreement between) spirit and sense by making themselves privileged regulators of the effectiveness of a peculiar effect, produced by the significant cognitive bond established between them.This original effect that, in its interactive comparison with the subject, usefully covers the object, places the ‘product’ on a market regulated by economic laws, but on the sole condition that it is not ‘consumed’ within it, that is to say that it maintains itself poietically operative in the recreational act of the relationship with the consumer.It produces non-objects, sensuous prototypes of sense, able to make themselves attractive products (with the double value of both use and exchange) before which the subject mimics – without distorting it – its own nature, putting it at the service of commerce (that is of its being with the product: cum merx).It is the Halo Effect. It necessarily precedes the formulation of any judgment because it is the regulatory precondition of every emotional production of common sense, which becomes an eminent contemporary device regulating the interaction between subject and object in the pre-vision of a possible knowledge of the world.